Pinus contorta Douglas ex Loudon and climate change: A literature review of opportunities, challenges, and risks in European forests - Stanislav Vacek; Zdeněk Vacek; Jan Cukor; Vilém Podrázský; Josef Gallo (Journal of Forest Science, 2022)
Lodgepole pine (Pinus contorta Douglas ex Loudon) was distributed from its natural range in western North America to different destinations, primarily to Europe (Scandinavia, British Islands), South America (Chile, Argentina), and New Zealand. It is used for its superior timber production and resistance to environmental conditions. This literature review paper consists of 150 references and presents a summary of research results dealing with the lodgepole pine potential in general with a specific focus on Europe from 1910 to 2022. It summarizes the importance, taxonomy, biological and ecological characteristics, site requirements, production and silviculture, risks and pests, as well as the potential of this tree species for forestry and the wood industry in relation to global climate change. Pinus contorta also has a considerable potential in Central Europe, especially at extreme sites with strong anthropogenic impact and in polluted regions. This tree species is very resistant to climatic factors and extreme events compared to other coniferous tree species. Moreover, its annual increment reached from 3 m3.ha-1.yr-1 on reclamation sites to 18 m3.ha-1.yr-1 in favourable environmental conditions. On the other hand, caution must be taken for possible invasive behaviour outside its natural range. Its importance can increase with ongoing climate change and the decline of native tree species.